(Un)Real Animals: Anthropomorphism and Early Learning About Animals. (22nd October 2015) - Geerdts, Megan S.
Abstract: Children are frequently exposed to anthropomorphic depictions of animals. The impact of anthropomorphism on children's development of factual and biological knowledge about real animals has consequences for how we engage children in early learning about the natural world. In this article, I discuss recent cross‐cultural and experimental studies on children's exposure to differing representations of animals, and studies that highlight the role that experiences with and about animals play in the development of biological reasoning and factual learning. Continued research that considers the conditions in which anthropomorphism may support early learning can explain discrepancies in previous research and help advance the ways we address the place of anthropomorphism in early educational experiences.